When Gains Loom Larger Than Losses - Harinck, Fieke; Van Dijk, Eric; Van Beest, Ilja; Mersmann, Paul (Psychological Science, 2007)
Previous research has generally shown that people are loss averse; that is, they weigh losses more heavily than gains. In a series of three experiments, we found that for small outcomes, this pattern is reversed, and gains loom larger than losses. We explain this reversal on the basis of (a) the hedonic principle, which states that individuals are motivated to maximize pleasure and to minimize pain, and (b) the assumption that small losses are more easily discounted cognitively than large losses are.